Again, i had mono and got behind...thank you

Smplify the expression for f(x):

1. f(x) = sin(cos^-1(x) + sin^-1(x))

2. f(x) = tan(pi + sin^-1(x))

sorry, i am not good at typing math...thanks for all your help

Printable View

- December 2nd 2008, 02:28 AMkrizzle13Simplify Inverse Trig Function
Again, i had mono and got behind...thank you

Smplify the expression for f(x):

1. f(x) = sin(cos^-1(x) + sin^-1(x))

2. f(x) = tan(pi + sin^-1(x))

sorry, i am not good at typing math...thanks for all your help - December 2nd 2008, 03:43 AMChop Suey
1. Easily done using the identities:

============

Let and let

2. Recall that and

==============

Let

Simply replace and you're done.